2023
DOI: 10.1186/s40494-023-01000-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of copper-gilded coronet ornaments excavated from a Sui or early Tang tomb situated in Xi’an, Shaanxi

Abstract: The formation of the gold layer in mercury gilding occurs through the heating a gold amalgam. As a result, the formation mechanism and technical characteristics of gilded products are closely related to the temperature at which they are heated. In this study, XRD and XPS analysis of a copper-gilded coronet from the Sui or Tang dynasties revealed that Au3Cu was one of the main phases of the gold layer. Therefore, base on the thermodynamic stability of ordered phases like Au3Cu, the estimated heating temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Particles with sizes greater than 1.0 µm accounted for approximately 0.218%, which is consistent with the results in ref. [28]. Furthermore, it was found that particles with sizes less than 0.5 µm accounted for about 98.4%.…”
Section: Distribution Of Atmospheric Particle Concentrationsmentioning
confidence: 94%
“…Particles with sizes greater than 1.0 µm accounted for approximately 0.218%, which is consistent with the results in ref. [28]. Furthermore, it was found that particles with sizes less than 0.5 µm accounted for about 98.4%.…”
Section: Distribution Of Atmospheric Particle Concentrationsmentioning
confidence: 94%